If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6r-7(4r+2)=28-8r
We simplify the equation to the form, which is simple to understand
6r-7(4r+2)=28-8r
Reorder the terms in parentheses
6r+(-28r-14)=28-8r
Remove unnecessary parentheses
+6r-28r-14=+28-8r
We move all terms containing r to the left and all other terms to the right.
+6r-28r+8r=+28+14
We simplify left and right side of the equation.
-14r=+42
We divide both sides of the equation by -14 to get r.
r=-3
| 10+5x-7=8x+8-3x | | 3x^3y+3x^2-9x^2y=0 | | 4.50+0.05x=0.2x | | 8n+2=-2n-8 | | p-38=47/5(h-7) | | -(2x-7)=7-2x | | 1-6n-1=18 | | 4y+2+6y-50=180 | | 3(-2x+1)-5=10 | | -2p+3=p+9 | | .5y-3=2y+12 | | s+6=4 | | -6=6x-6+x | | -(y-3)=2y+6 | | 4.50+0.05=0.20x-4.50 | | 4=-8.0n | | x+(26+x)=64 | | 5w^2+12w^2= | | 8(y-1)=3y+17 | | -5k-2k=14 | | -4-9/3=-7 | | -7(n+3)=-34+6n | | 64x^2-192x=0 | | 4.7=30 | | .4*-.03= | | 7x+22=11x+68 | | V-39=-17 | | 3=k+4+5 | | 21x+3=12x+6 | | -(1-7x)=4x-13 | | 2x^2-12x-27=0 | | 5=5-4s-7s |